2019
DOI: 10.1101/644633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human iPSC gene signatures and X chromosome dosage impact response to WNT inhibition and cardiac differentiation fate

Abstract: Non-genetic variability in human induced pluripotent stem cell (iPSC) lines impacts their differentiation outcome, limiting their utility for genetic studies and clinical applications. Despite the importance of understanding how non-genetic molecular variability influences iPSC differentiation outcome, large-scale studies capable of addressing this question have not yet been conducted. Here, we performed 258 directed differentiations of 191 iPSC lines using established protocols to generate iPSC-derived cardio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Of note, the iPSC-CMs showed slightly greater variation (i.e. lower correlation values) than the iPSCs, likely due to cellular heterogeneity [24][25][26] .…”
Section: Genetic Background Underlies Variability Of Molecular Phenotmentioning
confidence: 95%
See 3 more Smart Citations
“…Of note, the iPSC-CMs showed slightly greater variation (i.e. lower correlation values) than the iPSCs, likely due to cellular heterogeneity [24][25][26] .…”
Section: Genetic Background Underlies Variability Of Molecular Phenotmentioning
confidence: 95%
“…6b), we followed up three loci previously associated with heart rate (rs7612445, NC_000003.11:g.179172979G>T; rs8044595, NC_000016.9:g.15906130A>G; and rs6606689, NC_000012.11:g. 110975675T>C) and a potential novel locus (rs176107, NC_000005.9:g.89392662A>G) with additional experimental data (Supplementary Note). These data included Hi-C chromatin conformation maps from the same iPSC-CM samples 46 ( Supplementary Table 2a), and RNA-seq data from iPSC-CMs from an additional 128 whole-genome-sequenced subjects 26 , to examine associations between the putative causal NKX2-5 ASE-SNVs and expression of nearby or distal candidate target genes. For rs7612445 (98% PPA), which altered a T-box motif in the GNB4 locus, we validated that the two alleles have differential binding using EMSA, and that it is associated with differential expression in iPSC-CMs of several genes, including GNB4 (heart specific eQTL in GTEx) and MFN1 (influencing heart rate in zebrafish and Drosophila 15 ; Supplementary Fig.…”
Section: Nkx2-5 Ase-snvs Prioritize Causal Variants In Heart-rate Gwamentioning
confidence: 99%
See 2 more Smart Citations
“…It is unsurprising that, though we observed similar trends across three hiPSC lines, differences in differentiation outcomes were present. Recent work has shown that different hiPSC lines possess distinct transcription profiles and that these profiles are correlated with more or less cardiogenic hiPSC lines [21,22]. This may explain why some lines show more sensitivity to Wnt activation via Chiron compared to others.…”
Section: Plos Onementioning
confidence: 99%